Comparative Evaluation of Transthoracic Echocardiography and Multislice Computed Tomography in the Preoperative Assessment of Tetralogy of Fallot - Hoang, Van; Tra, Giang Tran; Van, Dong Tran; Dang, Duong Nguyen; Ngoc, Dung Tran (International Journal of Angiology, 2025)
Tetralogy of Fallot (TOF) is the most common cyanotic congenital heart disease, requiring precise anatomical assessment for optimal surgical planning. Transthoracic echocardiography (TTE) and multislice computed tomography (MSCT) are widely used imaging modalities for TOF evaluation, yet their relative diagnostic value, particularly in infants, remains an area of active investigation. This study aims to compare the diagnostic performance of TTE and MSCT in assessing intracardiac and extracardiac abnormalities in infants with TOF, with surgical findings as the reference standard.A prospective, single-center study was conducted on 35 infants diagnosed with TOF who underwent both TTE and 128-slice MSCT before surgical repair. Imaging findings were compared with intraoperative measurements, evaluating the sensitivity, specificity, and agreement (Cohen's kappa) between modalities.TTE and MSCT demonstrated comparable accuracy in assessing intracardiac abnormalities, with TTE showing slightly better agreement with surgical findings for ventricular septal defect (VSD) localization (κ = 0.581) than MSCT (κ = 0.485). Both modalities underestimated VSD size compared with intraoperative measurements, with MSCT showing a greater degree of underestimation (p < 0.001). In contrast, MSCT exhibited superior sensitivity in detecting extracardiac abnormalities, including coronary artery anomalies (100 vs. 50%) and major aortopulmonary collateral arteries (90 vs. 25%). While higher-generation MSCT scanners offer improved image resolution, the use of a 128-slice MSCT scanner proved to be a feasible alternative when more advanced technology is unavailable.TTE remains a reliable imaging modality for intracardiac assessment and is not inferior to MSCT in evaluating cardiac deformities in TOF. However, MSCT provides superior anatomical delineation of extracardiac structures, making it valuable for comprehensive preoperative planning. Despite its operator dependency, TTE remains the preferred first-line imaging tool due to its noninvasiveness and real-time functional assessment, whereas MSCT serves as a complementary modality, particularly for extracardiac evaluation. Further multicenter studies with larger cohorts are warranted to refine imaging protocols and optimize TOF assessment strategies in infants.
Keywords: tetralogy of Fallot; echocardiography; multidetector computed tomography